2008
DOI: 10.1007/s11695-007-9257-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Rhabdomyolysis After Open and Laparoscopic Roux-en-Y Gastric Bypass

Abstract: BS is safe, with low incidence of RML/ARF. High BMI is associated with a higher risk of RML. Probably a longer OT is associated with a higher risk of RML not statistically demonstrated in this study. The factors associated with a higher risk of CPK elevation were hypertension and open technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
2
15
2
Order By: Relevance
“…This result is consistent with Ettinger et.al [11] who described an incidence of 7% and in contrast with Mognol et al [12] and Lagandré et al [3], who reported an incidence of 22.7% and 26% respectively. A prolonged operative time is an important risk factor for the development of post-operative RML [3,11,12,14], indeed in our study, almost all the patients who developed RML had operative time ≥ 4 hours (5 out of 6, 83%). High BMI and arterial hypertension are potential risk factors for the development of RML.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is consistent with Ettinger et.al [11] who described an incidence of 7% and in contrast with Mognol et al [12] and Lagandré et al [3], who reported an incidence of 22.7% and 26% respectively. A prolonged operative time is an important risk factor for the development of post-operative RML [3,11,12,14], indeed in our study, almost all the patients who developed RML had operative time ≥ 4 hours (5 out of 6, 83%). High BMI and arterial hypertension are potential risk factors for the development of RML.…”
Section: Discussionsupporting
confidence: 92%
“…RML has been recognized as a complication of bariatric surgery. Recently, several retrospective and prospective studies described such complication in obese patients undergoing bariatric or general surgery [3,[10][11][12]. Probably RML following bariatric surgery is caused by a muscle pressure occurring during surgery which results in the creation of a compartmental syndrome [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 In some cases, surgical time may be reduced by planning a two-staged procedure. In cases where RML is suspected, high urine output should be promoted with the administration of intravenous fluids and diuretics before, during, and after surgery.…”
Section: Discussionmentioning
confidence: 99%